Communication complexity and data compression - (:unkn) unknown (My University, 2013)
A result of Ahlswede and Cai for the 2-party communication complexity of set intersection is generalized to a multiparty model. There are relations to several areas as to the direct-sum conjecture and amortized complexity in computational complexity or interactive communication in information theory as well as to wireless sensor networks and even quantum communication. The aim of the paper is mostly to survey these different applications and to draw the attention of researchers in one area to the results and applications in other areas. © 2013 IEEE.
Keywords: amortized complexity; communication complexity; functions on direct sums; prefix codes